EXPERIMENTAL STUDY OF THERMAL DEFORMATION IN A 3D-PRINTING PROCESS WITH POLYMER FILAMENT - Kobayashi, T.; Nishii, J.; Ishida, M.; Furumoto, H.; Utsumi, Y.; Kanematsu, H.; Gruescu, C. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Thermal deformation generated in a 3D-printing process was investigated mainly by the measurement of the radius of curvature. 3D-printing have been widely applied in industrial products. High end models of 3D-printer have heating and heat retention function to reduce thermal deformation and further they have sometimes equipped with a computational simulation code to predict the thermal deformation. In the present study, a predicting method of thermal deformation for a low end 3D-printer was investigated so that the investment for the equipment is minimized, then the following results were obtained. Dominating parameters were quantified by the measurement and multiple regression analysis of proto-typed products with different dimensions, that is, it was found that the parameters having greater influence on the deformation were in the order of the amount of filament, the length, the width, the height, bottom area, the volume and the manufacturing time, respectively. A simple but convenient regression equation was obtained which will be used for an estimation and simulation of the thermal deformation in production with the 3D-printer without using any expensive simulation code.